Access and Outcomes Among Hypertrophic Cardiomyopathy Patients in a Large Integrated Health System. Issue 3 (4th February 2020) - Thomas, Alexander; Papoutsidakis, Nikolaos; Spatz, Erica; Testani, Jeffrey; Soucier, Richard; Chou, Josephine; Ahmad, Tariq; Darr, Umer; Hu, Xin; Li, Fangyong; Chen, Michael E.; Bellumkonda, Lavanya; et al.
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy. Current guidelines endorse management in expert centers, but patient socioeconomic status can affect access to specialty care. The effect of socioeconomic status and specialty care access on HCM outcomes has not been examined. Methods and Results: We conducted a retrospective cohort study that examined outcomes among HCM patients receiving care in the Yale New Haven Health System between June 2011 and December 2017. Patients were assigned to lower or higher socioeconomic status groups (LSES/HSES) based on medical insurance provider and to receivers of specialty care (SC) at Yale's Inherited Cardiomyopathy clinic or general cardiology care (GC). The primary outcome was all‐cause death, and the secondary outcome was all‐cause hospitalization. We identified 953 HCM patients; 820 (86%) were HSES and 133 (14%) were LSES. Forty‐three (4.5%) patients died from cardiac and noncardiac causes. LSES patients within the general cardiology care cohort had significantly higher all‐cause mortality compared with HSES patients (adjusted hazard ratio, [95% CI]=10.06 [4.38–23.09]; P <0.001). This was not noted in the specialty care cohort (adjusted hazard ratio, [95% CI]=2.87 [0.56–14.73]; P =0.21). The moderator effect of specialty care on mortality difference between LSES versus HSES, however, did not reach statistical significance (hazard ratio, 0.29 [0.05–1.77]; P =0.18). Specialist care was associated with increased hospitalization (adjusted hazard ratio, [95% CI]=3.28 [1.11–9.73]; P =0.03 for LSES; 2.19 [1.40–3.40]; P =0.001 for HSES). Conclusions: Socioeconomically vulnerable HCM patients had higher mortality when not referred to specialty care. Further study is needed to understand the underlying causes.